Genetic variation associated with infection and the environment in the accidental pathogen Burkholderia pseudomallei - Chewapreecha, Claire; Mather, Alison E.; Harris, Simon R.; Hunt, Martin; Holden, Matthew T. G.; Chaichana, Chutima; Wuthiekanun, Vanaporn; Dougan, Gordon; Day, Nicholas P. J.; Limmathurotsakul, Direk; Parkhill, Julian; Peacock, Sharon J. (Nature Publishing Group UK, 2019)
Abstract: The environmental bacterium Burkholderia pseudomallei causes melioidosis, an important endemic human disease in tropical and sub-tropical countries. This bacterium occupies broad ecological niches including soil, contaminated water, single-cell microbes, plants and infection in a range of animal species. Here, we performed genome-wide association studies for genetic determinants of environmental and human adaptation using a combined dataset of 1,010 whole genome sequences of B. pseudomallei from Northeast Thailand and Australia, representing two major disease hotspots. With these data, we identified 47 genes from 26 distinct loci associated with clinical or environmental isolates from Thailand and replicated 12 genes in an independent Australian cohort. We next outlined the selective pressures on the genetic loci (dN/dS) and the frequency at which they had been gained or lost throughout their evolutionary history, reflecting the bacterial adaptability to a wide range of ecological niches. Finally, we highlighted loci likely implicated in human disease.
Funder: Thailand National Science and Technology Development Agency (FDA-CO-2562-8764-TH) and Thailand Science Research and Innovation fund (MRG6280226)
Funder: Food Standards Agency Fellow and is supported by the BBSRC Institute Strategic Programme Microbes in the Food Chain BB/R012504/1 and its constituent projects BBS/E/F/000PR10348 (Theme 1, Epidemiology and Evolution of Pathogens in the Food Chain) and BBS/E/F/000PR10351 (Theme 3, Microbial Communities in the Food Chain)
Keywords: Article; /631/208/205/2138; /631/181/2474; /631/326/325/2482; /45; /45/23; article